The Consortium of Celestials: Cosmic objects equitable interactions - Pravyana, Sekar Nabila Prajwalita Reka; Yatmo, Yandi Andri (Department of Architecture Faculty of Engineering Universitas Indonesia, 2024)
This speculative design study presents a provocative inquiry into the idea of an equitable society, addressed through the exploration of cosmic scale and celestial object interactions. The issues of injustice occurring in current society are influenced by the lack of access to resources and opportunities, where architecture also plays a part. Using a post-humanist approach, the study speculates on the scale of society, broadening the context of civilisation to develop an equitable society. The study creates a science narrative of a cosmic-scale civilisation as the basis of the architectural scheme between celestial objects in cosmic space that interacts in an equitable way. The narratives inform systems of architectural interactions that are designed to support an equitable life system, including communication, extraction, processing, and distribution of spatial and environmental resources. Five particular scenarios are outlined to demonstrate these interactions, from scenarios of resource exchange, climate calibration, and anticipation of destruction. This study demonstrates an important discussion on how design of an equitable society can be informed by the interactions between cosmic objects, systems, and resources. In doing so, this study introduces new narrative of architecture as a form of extraterrestrial built environment, expanding the current understanding of context and its environmental limitations.